MORPHOLOGICAL STUDY OF LUMINAL BREAST CANCER - M. V. Zavyalova; N. S. Telegina; S. V. Vtorushin; V. M. Perelmuter; E. M. Slonimskaya; E. V. Denisov; N. V. Cherdyntseva; S. V. Patalyak (Сибирский онкологический журнал)
Luminal A breast cancer has been shown to be characterized by the marked morphological heterogeneity. It is manifested by the variety of the infiltrative component structure of the primary tumor in which different structure types vary widely. The frequency of metastaticinvolvement of lymph nodes has appeared to associate with a variety of infiltrative component of the tumor and the presence of microalveolar structures in it. Neither morphological patterns of the lesion nor parameters of lymphogenic metastasis were associated with hematogenous dissemination, thus allowing no them to be considered as prognostic criteria.